Reflexões teóricas acerca da “crise ambiental”: possibilidades de novas orientações para as políticas públicas ambientais - José Irivaldo Alves Oliveira Silva (Ciências Sociais Unisinos)
The article presents a number of concerns that converge on the necessary analysis of environmental issues from a multi-center perspective, but privileging a political emphasis to understand the consequences of the environmental crisis in a risk society. It is a reflec-tive academic contribution that was not worked out with propositional claims, but may have practical consequences, including a reorientation of environmental policies based on the understanding of the society we live in. Therefore, the central objective of this study is precisely to address the phenomenon of globalization and its impact and the way in which we can understand it in its various forms. Then it examines environmental issues in a risk society as characterized by Beck, or in reflexive modernity as described by Giddens.